HUBUNGAN TEOLOGI BIBLIKA DENGAN DIVISI-DIVISI LAIN DALAM DISIPLIN ILMU TEOLOGI - Kusmanto, Fransius; Oci, Markus; Sugiono (STT Ekklesia Pontianak, 2023)
Abstract: The Bible is the holy book of Christians. In the academic field of theology, the Bible is the main capital of the book which is the subject that must be learned. Learn the Bible is not easy. There are many topics be the subject of discussion that must be learned, which make it difficult for readers to understand and relate one topic to another. This research is to find out the relationship between Biblical Theology and other branches of theology. To find out the results of the research, the method used is descriptive qualitative research method. In order to obtain good data, the authors use books and journal articles on the internet. The results obtained from this study are that the Bible is the main source and main guide in the academic field of theology. In discussing the Bible, there are branches of knowledge that must be understood. This is not to make it difficult to understand the Bible but to help make it easier to understand from every side of the division. There are four branches of Theology namely Systematic Theology, Practical Theology, Biblical Theology and Historical Theology. Biblical theology is the main bridge of many branches of theology in studying the Bible and this is the main concern of Academics to build good theology. Biblical theology has similarities and differences with other branches of theology in explaining the Bible. However, biblical theology relate with other divisions of theological sciences on explaining the Bible systematically. Accordingly, that theology and other divisions of knowledge in the field of theology help readers understand the Bible properly and correctly. By understanding several branches of theology in corelation, it can easily help Bible readers well based on every discussion that exists. Abstrak: Alkitab merupakan kitab suci orang Kristen. Di dalam bagian akademik bidang teologi, Alkitab menjadi modal utama buku yang menjadi subjek yang harus dipelajari. Mempelajari Alkitab bukanlah hal yang mudah. Banyak topik-topik yang menjadi pokok pembahasan yang harus dipelajari. Banyaknya topik-topik membuat para pembaca kesulitan memahami dan menghubungkan satu topik dengan yang lainnya. penelitian ini adalah untuk mengetahui hubungan Teologi Biblika dengan cabang ilmu teologi lainnya. Untuk mengetahui hasil dari penelitian yang dilakukan, metode yang digunakan adalah metode penelitian kualitatif deskriptif. Guna memperoleh data dengan baik, penulis menggunakan buku-buku dan artikel jurnal di internet. Hasil yang diperoleh dari penelitian ini adalah Alkitab menjadi sumber utama dan pegangan utama dalam bagian akademik bidang teologi. Dalam membahas Alkitab, ada cabang-canag ilmu yang harus dipahami. Hal ini bukan untuk mempersulit memahami Alkitab tetapi membantu mempermudah memahami dari setiap sisi divisi tersebut. Ada empat cabang ilmu Teologi yaitu Teologi Sistematika, Teologi Praktika, Teologi Biblikal dan Teologi Historika. Teologi Biblikal menjadi jembatan utama dari banyak cabang ilmu teologi dalam menelaah Alkitab dan hal ini menjadi perhatian utama dari Akademik untuk membangun teologi yang baik. Teologi biblikal memiliki persamaan dan perbedaan dengan cabang ilmu teologi lainnya dalam menjelaskan Alkitab. Namun demikian, Teologi biblikal memiliki hubungan dengan divisi ilmu teologi lainnya dalam menjelaskan Alkitab secara sistematis. Dengan demikian, Teologi dan divisi ilmu yang lain dalam bidang teologi membantu para pembaca memahami Alkitab dengan baik dan benar. Dengan memahami beberapa cabang ilmu teologi dalam hubungannya, dapat dengan mudah membantu para pembaca Alkitab dengan baik berdasarkan setiap pembahasan yang ada.